Seascapes' memories and construction of the Ego Conqueror: colonised coastal landscapes in the Southwest Pacific, 1884–1912. - Tiapa, Francisco (Postcolonial Studies, 2025)
The colonisation of the Southwest Pacific Islands was grounded in a narrative of racial superiority of the Australian and British colonisers. People from these islands sustained the sugar cane plantation in Queensland, where they were taken through Blackbirding, a method of people extraction that included negotiation, intimidation and violent imposition. This practice required a set of narratives of legitimisation spread through writings that went from academic publications to institutional documents. This article analyses the testimonies of Douglas Rannie, a colonial officer and sailor in charge of the extraction of workers from the Southwest Pacific Islands, and of their supervision and control in the Queensland colony. The first part presents an overall theoretical and methodological discussion added to a socio-historical context of the colonial construction of cultural seascapes in the Southwest Pacific. The second one is an analysis of the Douglas Rannie diaries of his navigation on the Pacific Islands and Queensland's coasts, with a focus on the construction of the past as a form of appropriation of these regions. The main axis is the construction of temporalities on the coastal landscapes as a form of colonial identity based on highlighting the achievements of colonisers on the Pacific seascapes.